HUMAN RIGHTS PERSPECTIVE ON IMPLEMENTING PRESIDENTIAL THRESHOLD IN INDONESIA - Kuswanto, Kuswanto (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
The current presidential election system has a threshold that must be met before being nominated as president and vice president. In Indonesia, the implementation of the presidential threshold concept began following the amendment of the 1945 Constitution, in which the President and Vice President are directly elected through public elections. This research aims to identify the implementation of the Presidential Threshold in Indonesia and the guarantee to fulfill human rights in its implementation. This research applies a normative juridical research method that discusses issues regarding the implementation of the presidential threshold and the extent to which human rights contribute to the presidential threshold in Indonesia. The findings of this research suggest that the implementation of the presidential threshold in the presidential and vice presidential elections is not considered a violation of human rights. Since human rights applied in Indonesia are not absolute human rights, the objective of implementing presidential thresholds in Indonesia is to generate leaders who receive majority political support to strengthen the presidential system. As a result, the government system is not prone to change.